2018
DOI: 10.3926/ic.1085
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of the current methodology for the study of the short-term liquidity problems in a sector

Abstract: Purpose: The aim of this work consists of defining and applying a new methodology for the calculation of short-term financial ratios that more reliably approximate the solvency of a sector. Design/methodology:We begin with a classic sector analysis and propose the creation of ratios that limit the debt repayment on an individual level and that do not imply the compensation of aggregate balances, as occurs with the current formulas of calculation. Findings:The new methodology more reliably approximates the solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…SMCs use to have a short-term management style, giving priority to management by liquidity, rather than to economic profitability (De Vries et al, 2009;Lakatos, 2020). The financial ratios, based on the financial information of the companies, allow an in-depth analysis of both the companies and the sector and allow the assessment of the situation of the sector in terms of short, medium-and long-term management (Bordeianu and Radu, 2020;Reyes-Ruiz and Hernández-Hernández, 2020;Rondós-Casas et al, 2018). In this study, the current liquidity ratio (Bordeianu and Radu, 2020) was used for the analysis of short-term and ROA (Bordeianu and Radu, 2020) from a medium-and long-term perspective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SMCs use to have a short-term management style, giving priority to management by liquidity, rather than to economic profitability (De Vries et al, 2009;Lakatos, 2020). The financial ratios, based on the financial information of the companies, allow an in-depth analysis of both the companies and the sector and allow the assessment of the situation of the sector in terms of short, medium-and long-term management (Bordeianu and Radu, 2020;Reyes-Ruiz and Hernández-Hernández, 2020;Rondós-Casas et al, 2018). In this study, the current liquidity ratio (Bordeianu and Radu, 2020) was used for the analysis of short-term and ROA (Bordeianu and Radu, 2020) from a medium-and long-term perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Those numbers are usually based on the Balance Sheet and/or the Statement of Profit and Loss. These financial ratios provide important information to strengthen the decision-making (Reyes-Ruiz and Hernández-Hernández, 2020;Rondós-Casas et al, 2018). They are powerful tools to help summarize financial statements and the health of a company or enterprise (Bordeianu and Radu, 2020).…”
Section: Liquidity Ratiosmentioning
confidence: 99%
“…The liquidity ratio is a ratio that shows the company's ability to fulfill its obligations or pay short-term money that must be fulfilled immediately. In other words, the liquidity ratio is a ratio that can be used to measure the extent of the company's ability to pay off its short-term obligations that are due soon (Pariyanti & Zein, 2018;Rondós-Casas et al, 2018). According to Hanafi & Halim (2016:75):…”
Section: Liquidity Ratiomentioning
confidence: 99%
“…This includes Box-Cox transformations (Ezzamel & Mar-Molinero, 1990;Mcleay & Omar, 2000;Watson, 1990), logarithmic transformations (Cowen & Hoffer, 1982;Deakin, 1976;Sudarsanam & Taffler, 1995), transformations by ranges (Kane et al, 1998), by square roots (Deakin, 1976;Frecka, & Hopwood, 1983;Martikainen et al 1995), by generalized risk box (Bahiraie, Azhar & Ibrahim, 2010), and other processing methods, such as weight of evidence (Nikolic et al 2013), outlier trimming (Ezzamel & Mar-Molinero, 1990;Frecka & Hopwood, 1983;Lev & Sunder, 1979;Martikainen et al, 1995;So, 1987;Watson, 1990), and outlier winsorization (Lev & Sunder, 1979). Rondós-Casas et al (2018) has shown the usefulness of an alternative methodology for calculating sector ratios. This provides more reliable information on the capacity of a sector to globally return its debt over the short term.…”
Section: Usefulness Of Sectoral Means In Financial Analyses Of Enterpmentioning
confidence: 99%